LANGUAGE STYLE OF RADEN ABIMANYU IN WAYANG ORANG SEKAR BUDAYA NUSANTARA ENTITLED “WAHYU CAKRANINGRAT’’ - MASFIROH, EMALUIN (Jurnal Ilmiah Mahasiswa FIB, 2013)
Language st yle is kind of language variation. In a particular occasion, people use different styles depends on to whom and where they speak, what the content of conversation is and the aim of the conversation. For example, language style which is used by a servant is different when speak to his/her boss and to other servants even though in one situation. It is because there are different social classes among them. Style brings complexity in using language in a community. In Javanese, its st yle is very complex because the speaker’s style deals with socialcontext. The writer wants to reveal Javanese language style through wayang orang because it is one of entertaining media that still can be used to learn Javanese language. There are two problems to be solved in this stud y, namely (1) what kind of Javanese language style and its stylist ic level which is used by Raden Abimanyu? (2) what is the dominant social factor that influences the using of Javanese language style b y Raden Abimanyu?This study is qualitative study because the writer wants to describe her finding of Raden Abimanyu’s language style towards other characters. The finding is explored and given the detail views of the topic.The result of the stud y shows that there are three kinds of Javanese language style which is used by Raden Abimanyu. They are ngoko, madya and krama. He used krama to the people that have high social class, they are Gatotkaca and Samba. Their stylistic level is the highest, level 3a. He used ngoko to the low class, Semar. Its stylistic level is t he lowest, 1. Moreover, he spoke madya style toward two people; the first is Gareng and the second is Gatotkaca. However, both of them are in different levels. In Gareng, his st ylistic level is 1a because it is almost similar to ngoko and toward Gatotkaca his st ylistic level is 3. In addition, it is found that there are three factors that influence his stylistic level. They are participant, topic and function. The participant is the most influencing factor. Here, Abimanyu consideredd about whom he spoke whether his addressee has high or low social class. However, he also considered the topic and the funct ion of the conversation. He smoothed his language if the topic was serious and the function was to ask an advice.The writer suggests to the reader especially who Javanese can understand and love their local language and used it appropriately to prevent Javanese from extinct ion. She also suggests to the next researcher to conduct the study about Javanese language style in another Javanese traditional theater for example Ketoprak and Ludruk or analyze other characters for example Semar who has unique identity. Keywords : Language st yle, wayang orang, social status.